A prospective cohort study of alcohol exposure in early and late pregnancy within an urban population in Ireland - BARRY, JOSEPH; MURPHY, DEIRDRE (My University, 2014)
Most studies of alcohol consumption in pregnancy have looked at one time point only, often relying on recall. The aim of this longitudinal study was to determine whether alcohol consumption changes in early and late pregnancy and whether this affects perinatal outcomes. We performed a prospective cohort study, conducted from November 2010 to December 2011 at a teaching hospital in the Republic of Ireland. Of the 907 women with a singleton pregnancy who booked for antenatal care and delivered at the hospital, 185 (20%) abstained from alcohol in the first trimester but drank in the third trimester, 105 (12%) consumed alcohol in the first and third trimesters, and the remaining 617 (68%) consumed no alcohol in pregnancy. Factors associated with continuing to drink in pregnancy included older maternal age (30-39 years), Irish nationality, private healthcare, smoking, and a history of illicit drug use. Compared to pre-pregnancy, alcohol consumption in pregnancy was markedly reduced, with the majority of drinkers consuming ≤ 5 units per week (92% in first trimester, 72-75% in third trimester). Perhaps because of this, perinatal outcomes were similar for non-drinkers, women who abstained from alcohol in the first trimester, and women who drank in the first and third trimester of pregnancy. Most women moderate their alcohol consumption in pregnancy, especially in the first trimester, and have perinatal outcomes similar to those who abstain.
PUBLISHED
Keywords: Alcohol exposure; Pregnancy; Neuroscience; Public health